2021
DOI: 10.1016/j.jbc.2021.100283
|View full text |Cite
|
Sign up to set email alerts
|

Acquired deficiency of peroxisomal dicarboxylic acid catabolism is a metabolic vulnerability in hepatoblastoma

Abstract: Metabolic reprogramming provides transformed cells with proliferative and/or survival advantages. Capitalizing on this therapeutically, however, has been only moderately successful because of the relatively small magnitude of these differences and because cancers may further adapt their metabolism to evade metabolic pathway inhibition. Mice lacking the peroxisomal bifunctional enzyme enoyl-CoA hydratase/3-hydroxyacyl CoA dehydrogenase (Ehhadh) and supplemented with the 12-carbon fatty acid lauric acid (C12) ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
(214 reference statements)
0
5
0
Order By: Relevance
“…EHHADH plays a prominent role in the peroxisomal beta-oxidation of long-chain fatty acids ( 52 ). A recent study found that downregulation of EHHADH resulted in accumulation of the toxic metabolite dodecanedioic acid (DDDA) and subsequent hepatic necrosis and might play a role in the development of HCC ( 53 ). ALDH5A1 is involved in the metabolism of the neurotransmitter 4-gamma-aminobutyric acid (GABA).…”
Section: Discussionmentioning
confidence: 99%
“…EHHADH plays a prominent role in the peroxisomal beta-oxidation of long-chain fatty acids ( 52 ). A recent study found that downregulation of EHHADH resulted in accumulation of the toxic metabolite dodecanedioic acid (DDDA) and subsequent hepatic necrosis and might play a role in the development of HCC ( 53 ). ALDH5A1 is involved in the metabolism of the neurotransmitter 4-gamma-aminobutyric acid (GABA).…”
Section: Discussionmentioning
confidence: 99%
“…The 3-hydroxy isomers formed by MFP-2 have the same (3R, 2R) configuration, or (24R, 25R) configuration in bile acid intermediates, underlining the role of MFP-2 in both pristanic acid degradation and bile acid synthesis [15]. Recently, it was demonstrated that LBP/MFP-1 is indispensable for the β-oxidation of dicarboxylic acids and the production of their medium-chain derivatives [6,15,17,18]. Peroxisomal β-oxidation pathways, including different enzymes and transporters.…”
Section: Peroxisomal β-Oxidation Systemsmentioning
confidence: 99%
“… 89 PolyA Single GepLiver-bulk-55 GSE156545 Wang, H. et al . 90 PolyA Paired For each bulk RNA-seq dataset included in GepLiver, the data source, related publication, library selection method and layout were provided in the table. PolyA: PolyA-selected; rRNA-d: rRNA-depleted; Paired: Paired-end; Single: Single-end.…”
Section: Methodsmentioning
confidence: 99%